A Review on Students' Comments Concerning factors affecting Their Absence in the Classroom - Razieh Nazari Vanani; Freshteh Aeen (Babol University of Medical Sciences, 2016)
BACKGROUND AND OBJECTIVE: Nowadays one of the educational problems is that, classes are not attractive enough to absorb students in the classroom. For this reason, the rate of absence of students has increased by irrational reasons. Therefore, this study was done with the aim of determination of effective factors on the absence of students in Shahre Kord University of Medical Sciences. METHODS: This descriptive cross-sectional study was performed on 120 students of Shahre Kord University of Medical Sciences in 2013 were selected using random sampling. For data collection, the data collection form was used. The collected data were analyzed by using SPSS and descriptive and inferential statistical tests. FINDINGS: According to the viewpoints of n=81 (67.5%) students participating in the research, inappropriate class time and from the viewpoints n=75 (62.5%) students, uniformity of classes and teaching methods play the most important role for being absent in and the least important factor in the absence of students in the classroom, which has been reported is classmates;#39 morality and behavior. Based on the chi-square test, there is no significant relationship between the effective factors on the absence of students with the field of study and GPA. CONCLUSION: Due to the inappropriate time classes are playing the most important role in the absence of students in the classroom, that is necessary the University professors pay more attention to use different strategies such as: changing the class time according to the majority of opinions, cause to achieve more and more participation and increase the essential abilities for this group of students in their learning environments.